Masyarakat Jawa Di Desa Sidomulio Kabupaten Padang Lawas Tahun 2007-2018 - Santi Agustina; Erniwati Erniwati (Jurnal Kronologi, 2023)
This study discusses the life of the Javanese people in Sidomulio Village, Barumun Selatan District, Padang Lawas Regency. This research aims to explain the life of the Javanese people in Sidomulio Village. Researcher Sources were obtained through literature studies in the form of articles, journals, study documents in the form of a collection of photographs displayed in the Sidomulio village head's office as well as field studies by means of interviews and observations. In the discussion there is much that we know that the arrival of the Javanese to Sidomulio can be said to be gradual. In 1945-1946 Sidomulio Village was pioneered by a prominent figure, Mr. Marsidin, Mr. Kasmin, Mrs. Kasiah, Mr. Suanda and their friends who were Javanese who moved to Sidomulio. The driving factors for Javanese migration in Sidomulio Village are geographical location, demography and the economy, while the pull factor is that there is still a large area of ​​land available for them to work on. The Javanese live with various aspects of their lives, so that the dominance of Javanese identity is found in Sidomulio Village. The Javanese interact well with the Mandailing community, as can be seen from the harmonious kinship between the two tribes. The harmonious relationship between the Mandailing-Javanese Batak people is shown when the Mandailing Batak people have a celebration, inviting the Javanese to attend it.